Sensor Ultrasonik HCSR04 Berbasis Arduino Due untuk Sistem Monitoring Ketinggian: Fitri Puspasari, Imam Fahrurrozi, Trias Prima Satya, Galih Setyawan, Muhammad Rifqi Al Fauzan, Estu Muhammad Dwi Admoko - Fitri Puspasari Fitri Puspasari; Imam Fahrurrozi Imam Fahrurrozi; Trias Prima Satya Trias Prima Satya; Galih Setyawan Galih Setyawan; Muhammad Rifqi Al Fauzan Muhammad Rifqi Al Fauzan; Estu Muhammad Dwi Admoko Estu Muhammad Dwi Admoko (Jurnal Fisika dan Aplikasinya, 2019)
At present the development of the digitalization world is growing. In length measurements generally can only be measured through manual measurement that measures the device that wants to know its length. However, now the world of digitalization is able to make measurements without touching the device to be measured. One of them is by utilizing sound wave sources or commonly referred to as ultrasonic waves. The purpose of this study was to prototype Arduino Due microcontroller digital distance measuring devices using HC-SR04 sensor. The research method used is literature study and direct observation. Measurement results are displayed in a computer device to facilitate reading. This design is controlled through Arduino Due. The prototype testing results of the tool can run well and can be accessed in real time.